Papers from the workshop on Bantu relative clauses: held in Paris on 8-9 January 2010 - Downing, Laura; Rialland, Annie; Beltzung, Jean-Marc; Manus, Sophie; Patin, Cédric; Riedel, Kristina (ZAS Papers in Linguistics, 2010)
All of the papers in the volume except one (Kaji) take up some aspect of relative clause construction in some Bantu language. Kaji’s paper aims to account for how Tooro (J12; western Uganda) lost phonological tone through a comparative study of the tone systems of other western Uganda Bantu languages. The other papers examine a range of ways of forming relative clauses, often including non-restrictive relatives and clefts, in a wide range of languages representing a variety of prosodic systems.